Cervical ectopic pregnancy: Mersilene tape in surgical management - A Bamigboye; O Ojo (South African Medical Association, 2014)
In view of the rarity of cervical ectopic gestation and the potentially high morbidity that may be associated with its presentation and management, we report management of a case of cervical ectopic pregnancy using cervical cerclage with Mersilene tape asÂ an intervention to reduce intraoperative haemorrhage during evacuation. The 36-year-old woman had a classic diagnosis of cervical ectopic pregnancy made in the consulting room with a transvaginal ultrasound examination. Evacuation with suction curettage was performed, and brisk bleeding was arrested with Mersilene tape. Placing a cervical cerclage is a relatively easy procedure to perform and may prevent major intraoperative bleeding, thereby minimising the risk of a major surgical procedure.